Author Correction: Laser-wakefield accelerators for high-resolution X-ray imaging of complex microstructures - Hussein, A E; Senabulya, N; Ma, Y; Streeter, M J V; Kettle, B; Dann, S J D; Albert, F; Bourgeois, N; Cipiccia, S; Cole, J M; Finlay, O; Gerstmayr, E; et al. (Scientific reports, 2020)
An amendment to this paper has been published and can be accessed via a link at the top of the paper.